Gamosa: Unique symbol of Assamese culture - Minti Gogoi
Gamosa woven with the aspirations of Assamese folk women, stands as a significant traditional textile item among the Assamese people. The original Assamese Gamosa is the special one with red colour border, white background and a horizontally placed floral design in one end and another end is woven with red colour stripes. While the origin of this age-old textile item of Assamese culture remains untraceable to date, it has deep roots in the local heritage. Now-a-days, its popularity is highly increased due to its utility and attractive colour combination. It enters the fashion market with its diversified application in both apparel and household sectors. This paper delves into various traditional Gamosa types, highlighting the importance of preserving their cultural essence and exploring future prospects and explores the pivotal significance of Geographical Indication (GI) tagging in safeguarding and promoting the cultural heritage of Assamese Gamosa, shedding light on the unique characteristics and historical resonance encapsulated in this traditional textile.